Perception and satisfaction regarding an intradialytic virtual reality exercise program in Brazil - Marcelly Oliveira Pinton; Bruno Valle Pinheiro; Fabrício Sciammarella Barros; Daniele Thomé Silva; Ana Paula de Lima Souza Dias; Maria Clara de Lima Assis; Emanuele Poliana Lawall Gravina; Leda Marília Fonseca Lucinda; Eva Segura Orti; Maycon Moura Reboredo (Brazilian Journal of Nephrology)
Abstract Introduction: Virtual reality (VR) has been used as an effective tool for improving patient adherence to intradialytic exercise programs. This study evaluated the perception and satisfaction of patients and healthcare professionals regarding an intradialytic VR exercise program. Methods: The VR protocol included lower limb resistance and endurance training. Patients’ perception and satisfaction, as well as the perception of healthcare professionals, were assessed using questionnaires. Results: Of the 27 patients who participated in the exercise program, most evaluated the experience as very good and easy to perform. Of the 24 patients who completed the program, most described the experience as beneficial. Most of the healthcare professionals reported that the protocol did not affect their work routine. Conclusion: The intradialytic VR exercise program was well accepted by patients and healthcare professionals.